Acquisition Of Arabic Language In SMAIT Baitul Muslim - Muin, Muhamad Fatkhul; Ian Antono (Himpunan Mahasiswa Program Studi (HMPS) Pendidikan Bahasa Arab Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Jember, 2024)
The purpose of this study was to see how Arabic language acquisition in SMAIT Baitul Muslim. This study examines the methods applied by educational institutions to help students learn Arabic. The purpose of this study was to improve the understanding of the Arabic learning process through a combination of observation, teacher and student interviews, and literature review. Based on research findings, Arabic language teaching at SMAIT Baitul Muslim uses interesting and dynamic teaching methods such as role plays, language games, and group discussions. Students' language proficiency is enhanced through Arabic extracurricular activities and language development activities such as the Language Glory Vaganza (LGV) and the Center of Language Improvement (CLI). Learning is influenced by various factors, including environmental support, learning styles, and student motivation. Students at SMAIT Baitul Muslim find learning Arabic interesting and rewarding, although there are still a number of challenges. This highlights the importance of innovative teaching strategies in improving Arabic language acquisition.